2023
DOI: 10.1159/000533912
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies in Hormone Receptor and HER2 Expression between Malignant Serous Effusions and Paired Tissues from Primary or Recurrent Breast Cancers

Ilias P. Nikas,
Sojung Lim,
Seock-Ah Im
et al.

Abstract: Objectives: Immunohistochemistry (IHC) for the estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2) biomarkers has prognostic and therapeutic value in breast cancer, while it facilitates molecular subtyping. This study aimed to identify subtype discordance and its clinical significance among different phases of breast cancer evolution, focusing on effusion cytology samples diagnosed with malignancy. Methods: Our electronic archive was searched for all effusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…Mouse monoclonal antibodies A45-B/B3 directed against pancytokeratin (Micromet, Munich, Germany) and keratin 8/18 Ab-1 (Thermo Fisher Scientific, Fremont, CA, USA) and mouse monoclonal antibody directed against c-erbB-2 (Her-2/neu) (BioGenex, Fremont, CA, USA) were used. For cytokeratin staining, two slides with 1.5 × 10 6 cells per patient were evaluated, according to the consensus recommendations for standardized tumor cell detection [ 13 ]. DTC positivity was defined as at least one pancytokeratin-positive cell with typical cell morphology [ 45 ] per 1.5 × 10 6 cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mouse monoclonal antibodies A45-B/B3 directed against pancytokeratin (Micromet, Munich, Germany) and keratin 8/18 Ab-1 (Thermo Fisher Scientific, Fremont, CA, USA) and mouse monoclonal antibody directed against c-erbB-2 (Her-2/neu) (BioGenex, Fremont, CA, USA) were used. For cytokeratin staining, two slides with 1.5 × 10 6 cells per patient were evaluated, according to the consensus recommendations for standardized tumor cell detection [ 13 ]. DTC positivity was defined as at least one pancytokeratin-positive cell with typical cell morphology [ 45 ] per 1.5 × 10 6 cells.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies showed that molecular characteristics can vary between the primary tumor (PT) and distant metastases [ 12 , 13 , 14 ]. More specifically, discrepancies in HER2 expression between the PT and metastases could be shown in almost 50% of cases [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%